A Study to Assess the Effectiveness of Cradle Hold Position on the Gratification During Breastfeeding Among Postnatal Mothers Admitted at Selected Maternity Hospitals in South Bangalore, Karnataka - N. Sucharitha (International Journal of Women's Health Nursing And Practices, 2024)
This study aims to assess the effectiveness of the cradle hold position on the satisfaction experienced during breastfeeding among postnatal mothers admitted at selected maternity hospitals in south Bangalore, Karnataka. The cradle hold position is a commonly used breastfeeding technique where the mother supports the baby's head with one hand and holds the baby's body with the other arm, bringing the baby's mouth to the breast. The level of satisfaction during breastfeeding is an important aspect of postnatal care as it can influence maternal confidence, bonding between mother and baby, and overall breastfeeding success. The study employs a quantitative research approach with a pre-experimental design. The sample consists of postnatal mothers who have recently given birth and are currently breastfeeding their infants. Data were collected using a structured questionnaire to assess satisfaction levels before and after implementing the cradle hold position. Descriptive and inferential statistics were used to analyze the data. The findings of this study will contribute to the understanding of the impact of the cradle hold position on maternal satisfaction during breastfeeding, which can inform maternity care practices and improve postnatal care for mothers and infants
Keywords: Breastfeeding; Cradle hold position; maternal satisfaction; postnatal care; structured questionnaire